Subcellular RNA profiling links splicing and nuclear DICER1 to alternative cleavage and polyadenylation - Neve, Jonathan; Burger, Kaspar; Li, Wencheng; Hoque, Mainul; Patel, Radhika; Tian, Bin; Gullerova, Monika; Furger, Andre (Genome Research, 2016)
Alternative cleavage and polyadenylation (APA) plays a crucial role in the regulation of gene expression across eukaryotes. Although APA is extensively studied, its regulation within cellular compartments and its physiological impact remains largely enigmatic. Here, we used a rigorous subcellular fractionation approach to compare APA profiles of cytoplasmic and nuclear RNA fractions from human cell lines. This approach allowed us to extract APA isoforms that are subjected to differential regulation and provided us with a platform to interrogate the molecular regulatory pathways that shape APA profiles in different subcellular locations. Here, we show that APA isoforms with shorter 3′ UTRs tend to be overrepresented in the cytoplasm and appear to be cell-type–specific events. Nuclear retention of longer APA isoforms occurs and is partly a result of incomplete splicing contributing to the observed cytoplasmic bias of transcripts with shorter 3′ UTRs. We demonstrate that the endoribonuclease III, DICER1, contributes to the establishment of subcellular APA profiles not only by expected cytoplasmic miRNA-mediated destabilization of APA mRNA isoforms, but also by affecting polyadenylation site choice.